Pengaruh Perbedaan Asal Sekolah dan Motivasi Belajar Terhadap Pemahaman Konsep Dasar Akuntansi Mahasiswa Program Studi Pendidikan Akuntansi STKIP PGRI Sumatera Barat - Sherly Ganda Putri; Yesmira Syamra; Indra Mulia Pratama (Horizon, 2021)
This study aims to analyze: 1.) To analyze differences in school origin affect the understanding of basic accounting concepts 2.) To analyze learning motivation affect the understanding of basic accounting concepts 3.)      To analyze Differences in school origin and learning motivation have an effect on understanding the basic concepts of accounting. This type of research is associative and descriptive. The population of this study were students of the STKIP PGRI West Sumatra Accounting Education Study Program class 2017, 2018, and 2019 which amounted to 114 people. The sampling technique used is proportional random sampling with a total sample of 89 people. Data analysis using multiple linear regression analysis and hypothesis testing using f test and t test. Data analysis was assisted by SPSS version 15 and eviews version 8. The results showed that: 1.) Differences in school origin had no positive and significant effect on understanding the basic concepts of accounting. 2.) Learning motivation has a positive and significant effect on understanding the basic concepts of accounting. 3.) Differences in school origin and learning motivation have an effect on understanding the basic concepts of accounting.